2022
DOI: 10.1002/smll.202206295
|View full text |Cite
|
Sign up to set email alerts
|

Defect Healing in Graphene via Rapid Thermal Annealing with Polymeric “Nanobandage”

Abstract: Overcoming throughput challenges in current graphene defect healing processes, such as conventional thermal annealing, is crucial for realizing post‐silicon device fabrication. Herein, a new time‐ and energy‐efficient method for defect healing in graphene is reported, utilizing polymer‐assisted rapid thermal annealing (RTA). In this method, a nitrogen‐rich, polymeric “nanobandage” is coated directly onto graphene and processed via RTA at 800 °C for 15 s. During this process, the polymer matrix is cleanly degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…We also revealed that the thermal treatment 10–16 of NPC s at high temperatures under an inert atmosphere affords the corresponding NPG s by fusing the H-terminated edges, 2,17 and this is the origin of the electrochemical stability of NPG s. This annealing following the CH 4 -CVD synthesis will also improve the integrity of the graphene architecture by reducing the defect concentration, which is helpful to develop stable electrochemical devices using NPG s such as long-lived air–metal batteries etc. 18 The quantitative evaluation of the defect type and concentration before/after annealing will be a starting point for the development of state-of-the-art continuous porous carbon materials based on NPG chemistry, 1,2 but recent investigations on the structural changes upon annealing by changing the size of templates 16,19 gave us a qualitative picture.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…We also revealed that the thermal treatment 10–16 of NPC s at high temperatures under an inert atmosphere affords the corresponding NPG s by fusing the H-terminated edges, 2,17 and this is the origin of the electrochemical stability of NPG s. This annealing following the CH 4 -CVD synthesis will also improve the integrity of the graphene architecture by reducing the defect concentration, which is helpful to develop stable electrochemical devices using NPG s such as long-lived air–metal batteries etc. 18 The quantitative evaluation of the defect type and concentration before/after annealing will be a starting point for the development of state-of-the-art continuous porous carbon materials based on NPG chemistry, 1,2 but recent investigations on the structural changes upon annealing by changing the size of templates 16,19 gave us a qualitative picture.…”
Section: Introductionmentioning
confidence: 82%
“…1,3 The use of relatively inert CH 4 9 as the gaseous carbon source is crucial for kinetically achieving the formation of mono-layered carbon. 1 We also revealed that the thermal treatment [10][11][12][13][14][15][16] of NPCs at high temperatures under an inert atmosphere affords the corresponding NPGs by fusing the H-terminated edges, 2,17 and this is the origin of the electrochemical stability of NPGs. This annealing following the CH 4 -CVD synthesis will also improve the integrity of the graphene architecture by reducing the defect concentration, which is helpful to develop stable electrochemical devices using NPGs such as long-lived airmetal batteries etc.…”
Section: Introductionmentioning
confidence: 86%
“…1,3 The use of relatively inert CH4 9 as the gaseous carbon source is crucial for kinetically achieving the formation of mono-layered carbon. 1 We also revealed that the thermal treatment [10][11][12][13][14][15][16] of NPCs at high temperatures under an inert atmosphere affords the corresponding NPGs by fusing the H-terminated edges, 2,17 and this is the origin of the electrochemical stability of NPGs. This annealing following the CH4-CVD synthesis will also improve the integrity of the graphene architecture by reducing the defect concentration, which is helpful to develop stable electrochemical devices using NPGs such as long-lived air-metal batteries etc.…”
Section: Introductionmentioning
confidence: 86%
“…11 Further advancements have been made to incorporate an adhesive moiety, 9 spatial control of dopants via block copolymer (BCP) self-assembly, 8,12 dendrimers, 16,17 brushes, [18][19][20] and micelles. 8 Recently, Senger et al extended the polymeric spin-on doping approach to healing defective graphene by doping nitrogen, 21 suggesting that this approach has an enormous opportunity for other classes of materials, not only for traditional semiconductors.…”
Section: Doping Of Hard Materialsmentioning
confidence: 99%
“…However, there might be unexplored chemical structures, which are not used in SAMs for monolayer doping. For instance, a recent work by Senger et al demonstrated commercially available, branched polyethylenimine as a polymeric nitrogen dopant, 21 suggesting an immense opportunity to design new polymeric dopants that are not accessible by small molecular synthesis.…”
Section: Polymer Chemistrymentioning
confidence: 99%